Global health without sexual and reproductive health and rights? Analysis of United Nations documents and country statements, 2014–2019 - Salla Atkins; Lynda Gilby; Meri Koivusalo (BMJ Global Health, 2021)
Introduction The initial International Conference on Population and Development in 1994 contains the first reference to sexual and reproductive health and reproductive rights (SRHR). It has been considered agreed language on SRHR in future United Nations (UN) documents. However, opposition to SRHR in global forums has increased, including in conjunction with an increase in religious, far-right populist politics. This study provides an empirical analysis of UN documents to discover whether opposition to SRHR has resulted in changes in the language on SRHR between and what these changes are.Methods This is a qualitative policy analysis in which 14 UN resolutions, 6 outcome documents from the Commission on the Status of Women (CSW) and 522 country and group statements and 5 outcome reports from the Commission on Population and Development were collected from the organisations websites from 2014 to 2019. Framework analysis was used. The text from documents was charted and indexed and themes developed from these.Results The results demonstrated a disappearance of the language on abortion in the CSW outcome documents from 2017 and a change in the language on comprehensive sexuality education in the CSW as well as the UN General Assembly resolutions from 2018. This change included a removal of ‘sexuality’ to an increased emphasis on the role of families. Furthermore, documents showed an inability of some states to accept any mention of sexual and reproductive health at all, expanding from the usual contestations over abortion.Conclusion Our findings suggest that the global shift in politics and anti-SRHR actors at UN negotiations and conferences have removed previously agreed on language on SRHR from future UN resolutions and outcome documents. This is a concern for the global realisation of SRHR.